3 - Possibilidades e limites ao exercício da Liberdade Sindical em Cabo Verde de 1975 a 2014 - Osvaldo de Carvalho Cruz (Africa Development, 2025)
This article, which is based on qualitative research carried out in Cape Verde, aims to analyze whether there is a possible contradiction in the Cape Verdean labor market, between the legal and institutional conditions that facilitate the exercise of freedom of union and some social and political practices that limit them and are imposed on unions and workers by successive governments and companies. The situations that limit the exercise of freedom of association contribute to the reduction of the socioeconomic security of Cape Verdean workers, who face, in many moments and contexts work, situations of precariousness and informality, combined with the possibility of losing their jobs, in a context in which the unemployment level, especially in youth, is high.